The Origins of Czech Academic Lexicography. From Foreign Inspiration to State Formation Potential - Věra Dvořáčková (Studi Slavistici)
This paper deals with the beginnings of Czech academic lexicography in the context of contemporary international lexicography. When work on the first dictionary covering the contemporary Czech vocabulary commenced, many other lexicographic projects were under way in Europe, frequently not comparable in terms of staffing and funding. The authors of the Czech dictionary were able to learn from the experience of their colleagues abroad, which helped them understand what could be useful in the context of the Czech language, what sources of inspiration could be drawn on, and where greater account should be taken of specific local circumstances. The compilation of the Reference Dictionary of the Czech Language was also substantially influenced by the establishment of the independent Czechoslovak Republic in 1918. In light of its multi-national population, in particular the numerous German and Hungarian minorities, the republic conceived the compilation of an extensive dictionary of the Czech language as a project with significant potential for state formation.